Lei Maria da Penha e prática policial: vivências em uma delegacia especializada no município de Recife, PE. - Guedes, Daniella Maria Brito Azedo (2018)
The law nº. 11.340/2006, known as Lei Maria da Penha (LMP), represented a milestone in addressing domestic violence, bringing at the same time prevention mechanisms, public policy guidelines, the possibility of applying protective measures, and the resurgence in the treatment of criminal offenses (crimes and contraventions) practiced against womans in domestic environment. In its punitive aspect, the exacerbation occurred by virtue of article 41 of the aforementioned Law that modified the procedure of crimes of less offensive potential, by prohibiting the incidence of Law 9,099 / 1995 when dealing with domestic or family violence, and consequently closed the application of the decriminalizing institutes. In his art. 44, increased the penalty of article 129, § 9 of the Penal Code, expurgating once and for all "light" bodily injury as inserted in the concept of offense of lesser offensive potential, since the sentence went to 3 (three) years, innovating with a criminal type in late 2017, where non-compliance with the protective measure became a crime. In addition to the punitive aspect, Law no. 11,340 / 2006 was innovative in catalyzing a series of institutional changes by offering specialized care for that woman who seeks the statewide network of care, and it is at this point that the interest of knowing the police institution's action arises, because when it is not the first, it is one of the first official alternatives of the woman who seeks to end a situation of violence. At this point, the LMP brings an extension to the functions of the institution of the civil police, originally and primarily investigative - repressive, to welcome the woman in a situation of violence and insert her in the service network. Thus, it seeks to understand if the purposes of Law 11.340 / 2006, regarding the protection of women in situations of domestic violence that seeks assistance by the police authority, is effective. From the theoretical lens of critical criminology, which starts from the delegitimization of the official discourse of criminal law and its institutions, and from the sociology of violence, specifically that which tries to understand the phenomenon of violence worked by institutions, it was sought to understand the operation of the specialized police unit of domestic violence through the observation in loco in the municipality of Recife. As a way of understanding the perceived autonomy in police practice, semi-structured interviews were conducted with state managers, in order to understand the extent to which police are thought of in the public policy nucleus of the State of Pernambuco. It has been observed from the observations that the police act within a spectrum of autonomy and informality, not necessarily resulting in something negative from the perspective of the victim, since certain practices are revealed as a different alternative from the demand for punishment, such practices show how the police and their structure are not prepared to welcome the woman into the care network, often reproducing stigmatizations for a common clientele of victims and perpetrators. In the interviews with the police managers, the Women's Secretariat and the Department of Management and Planning, the absence of a truly dialogic relationship was observed, since within the evaluation of the police institution, the State is mainly concerned with the indices collected, mainly the data on Violent and Lethal Crimes (VLC’s), leaving aside other crimes, which are the majority, outside the reach the state. In relation to such crimes, the police are the ones who make the front line and it is clear their autonomy before these organs that have "confidence" in the police action,and this makes the services offered by it do not have the qualification and specialization that the LMP determines, and the ideal of integral reception by the service network is far from being realized within the Criminal Justice System.